Demand forecast in a small restaurant - Caixeta, André Fernandes; Fernandes, Nilson José; Nunes, Deivid Marques; Santos, Aline Gonçalves do (Brazilian Journal of Production Engineering, 2023)
Production Planning and Control (PPC) determines the dimensioning of resources, as well as the identification of the layout that best suits the production flow. Demand forecasting, being one of the main activities of the PPC, proves to be an important management tool to support decision-making. The present work makes a comparative analysis of the application of demand forecasting techniques in a small restaurant in the interior of the state of Mato Grosso/BR, with the objective of efficiently predicting the number of meals. Quantitative analyzes of the research were carried out using Excel® software, in which demand forecasts and the respective associated errors were determined. After the analysis, the method that obtained the best performance was the weighted moving average with 3 forecast periods and weights of 25%, 35% and 40% in these periods. Other methods analyzed (simple moving average and exponential moving average) also achieved acceptable results, that is, with reduced forecasting errors.